Headmaster’s Strategy in Developing Environmental Care Character at SMA Negeri 9 Rejang Lebong - Sanjaya, Ronald (Yayasan Corolla Education Centre, 2021)
This study aims to describe the headmaster’s strategy in developing students’ environmental care character. This study is descriptive qualitative. Subject of the study was SMA Negeri 9 Rejang Lebong’s headmaster. The research data were obtained by observation, interview and documentation. The data validity examination was used credibility test with triangulation. The data was analyzed by using data reduction, data display and drawing conclusion. Based on research result it can be explained that SMA Negeri 9 Rejang Lebong use strategies in developing students’ environmental care character, those are: teaching-learning process, school culture, extracurricular and parents reinforcement. Moreover, environmental care behavior is reflection of understanding and ability to apply it in daily life. Students’ behavior as the researcher explained such as garbage disposing in the appropriate place, daily picket activities and paying attention to social care for school elements and the environment